Effects of climatic factors on fruit quality of Siraitia grosvenorii and its molecular regulation mechanism - PENG Huan1, MO Changming2, XIE Lei3, LUO Zuliang3, GUO Wenfeng2, TANG Qi4, XIAO Dong1* (Guangxi Zhiwu)
In order to investigate the impact of climatic factors on the quality of Siraitia grosvenorii fruits pollinated in different seasons and the underlying molecular mechanism involved, the differences in climate factors, quality traits, and gene expression between fruits of the main cultivar S. grosvenorii “Qingpiguo” pollinated in summer and autumn were statistically analyzed by monitoring climate factors at different developmental stages, measuring morphological changes, detecting mogroside metabolism, and analyzing gene expression using qRT-PCR. The results were as follows:(1)Compared to summer-pollinated fruits, the average temperature and effective accumulated temperature of autumn-pollinated fruits decreased significantly after 35 d. Additionally, the temperature difference between day and night increased significantly before 65 d. However, this difference was still less than that of the average temperature and effective accumulated temperature. The light intensity and air humidity remained similar.(2)The transverse diameters, longitudinal diameters, and single fruit weights of autumn-pollinated fruits increased compared to those of summer-pollinated fruits, however, these differences were not statistically significant.(3)Mogroside V and 11-O-mogroside V in autumn-pollinated fruits accumulated slowly from 55 d with a delay of about 10 d, moreover, the content of both compounds in ripe fruits decreased by 40.66% and 46.07%, respectively.(4)In autumn, the number and extent of up-regulated mogroside V synthetase genes were relatively lower, and their co-expression consistency was poorer than in summer. Furthermore, the glucosyltransferase gene SgUGT94-289-3 which was responsible for the final step in mogroside V biosynthesis, exhibited down-regulation at all time points of 55 d. In summary, the shape and size of S. grosvenorii fruits pollinated in different seasons were not significantly affected by climatic factors; however, the content of mogroside V was significantly influenced by the temperature, which potentially influences these variations in mogroside V by regulating both the co-expression consistency and expression level of mogroside V synthetase genes. The results of this study provide the theoretical reference for high-quality cultivation and genetic breeding of S. grosvenorii.